PENGARUH ENDORSER TERHADAP PERSEPSI DAN KEPUTUSAN PEMBELIAN SEPATU OLAHRAGA SPECS INDONESIA - FAISHAL ABDI SAPUTRA; PAMASANG S. SIBURIAN; ASNAWATI - (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The purpose of this research was to verify the effect of endorser election, toward perception and the decision of purchase of sport shoes Specs Indonesia. To collected the data research, research used Random Sampling and Accidential Sampling Method. The sample which used in this research was 60 respondent with the criteria of all men who using sport shoes Specs Indonesia. This research used multiple linear regression analysis with SPSS as an instrument to calculate data. The result showed that there was  a positive and significantbetween endorser election toward perception and the decision of purchase.Keywords: Endorser, Perception The Decision of Purchase